Bilateral political relations and sovereign wealth fund investment - Knill, April; Lee, Bong-Soo; Mauck, Nathan (Journal of Corporate Finance, 2012)
We examine the role of bilateral political relations in sovereign wealth fund (SWF) investment decisions. Our empirical results suggest that political relations play a role in SWF decision making. Contrary to predictions based on the FDI and political relations literature, we find that relative to nations in which they do not invest, SWFs prefer to invest in nations with which they have weaker political relations. Using a two-stage Cragg model, we find that political relations are an important factor in where SWFs invest but matter less in determining how much to invest. Inconsistent with the FDI and political relations literature, these results suggest that SWFs behave differently than rational investors who maximize return while minimizing risk. Consistent with the trade and political relations literature, we find that SWF investment has a positive (negative) impact for relatively closed (open) countries. Our results suggest that SWFs use—at least partially—non-financial motives in investment decisions.